The role of parental embrace in children's pain management during invasive procedures: A systematic review - Aronggear, Nona Mulyani; Allenidekania, Allenidekania; Nurhaeni, Nani; Adawiyah, Robiyatul (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Children undergoing invasive procedures in hospitals, such as IV insertion or injection, often experience significant pain and anxiety, especially in critically ill children. Non-pharmacological interventions such as parental holding have been studied as an effective approach in reducing children's pain responses during procedures. Purpose: To analyze the scientific evidence regarding the role of parental holding in pain management in children during invasive procedures, including in critically ill children. Method: A search was conducted through PubMed, Scopus, and ScienceDirect databases following PRISMA guidelines. Inclusion criteria included RCT design, population of children undergoing invasive procedures, parental holding intervention, and outcomes in the form of pain intensity and/or anxiety. A total of 1,324 articles were identified, while 8 studies met the criteria and were analyzed narratively. Results: Showed that parental holding is effective in reducing children's pain and anxiety, as well as increasing emotional comfort for both children and parents. Despite its proven benefits, implementation of this intervention is still limited in clinical practice and lacks standardized guidelines, especially in pediatric intensive care units. Conclusion: Parental hugs have been shown to be effective in reducing procedural pain in infants and children during invasive procedures.